Fabrication and characterization of ZnO nanostructures for DNA detection - Foo, Kai Loong (School of Nano Electronic Engineering, 2013)
The aim of this research work is to synthesis, fabricate, and characterize ZnO nanostructures based sensor for DNA immobilization and hybridization detection.